A human protein hydroxylase that accepts D-residues - Choi, H; Hardy, AP; Leissing, TM; Chowdhury, R; Nakashima, Y; Ge, W; Markoulides, M; Scotti, JS; Gerken, PA; Thorbjornsrud, H; Kang, D; Hong, S; et al. (Springer Nature, 2020)
Factor inhibiting hypoxia-inducible factor (FIH) is a 2-oxoglutarate-dependent protein hydroxylase that catalyses C3 hydroxylations of protein residues. We report FIH can accept (D)- and (L)-residues for hydroxylation. The substrate selectivity of FIH differs for (D) and (L) epimers, e.g., (D)- but not (L)-allylglycine, and conversely (L)- but not (D)-aspartate, undergo monohydroxylation, in the tested sequence context. The (L)-Leu-containing substrate undergoes FIH-catalysed monohydroxylation, whereas (D)-Leu unexpectedly undergoes dihydroxylation. Crystallographic, mass spectrometric, and DFT studies provide insights into the selectivity of FIH towards (L)- and (D)-residues. The results of this work expand the potential range of known substrates hydroxylated by isolated FIH and imply that it will be possible to generate FIH variants with altered selectivities.